Mixed-linker UiO-66: structure–property relationships revealed by a combination of high-resolution powder X-ray diffraction and density functional theory calculations - Marco Taddei (Physical Chemistry Chemical Physics, 2017)
The use of mixed-linker metal–organic frameworks (MIXMOFs) is one of the most effective strategies to modulate the physical–chemical properties of MOFs without affecting the overall crystal structure. In many instances, MIXMOFs have been recognized as solid solutions, with random distribution of ligands, in agreement with the empirical rule known as Vegard's law. In this work, we have undertaken a study combining high-resolution powder X-ray diffraction (HR-PXRD) and density functional theory (DFT) calculations with the aim of understanding the reasons why UiO-66-based amino- and bromo-functionalized MIXMOFs (MIXUiO-66) undergo cell expansion obeying Vegard's law and how this behaviour is related to their physical–chemical properties. DFT calculations predict that the unit cell in amino-functionalized UiO-66 experiences only minor expansion as a result of steric effects, whereas major modification to the electronic features of the framework leads to weaker metal–linker interaction and consequently to the loss of stability at higher degrees of functionalization. For bromo-functionalized UiO-66, steric repulsion due to the size of bromine yields a large cell expansion, but the electronic features remain very similar to pristine UiO-66, preserving the stability of the framework upon functionalization. MIXUiO-66 obtained by either direct synthesis or by post-synthetic exchange shows Vegard-like behaviour, suggesting that both preparation methods yield solid solutions, but the thermal stability and the textural properties of the post-synthetic exchanged materials do not display a clear dependence on the chemical composition, as observed for the MOFs obtained by direct synthesis.